Impact of Utilizing Social Media, Perceived Competitive Value on MSMES Performance through Partnerships - Junaidi, Junaidi; Lubis, Zulkarnain; Effendi, Ihsan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study is to determine the role of partnerships in mediating the use of social media and perceived competitive value on the performance of MSMEs. The approach in this research is associative. As for the population in the study, namely MSMEs assisted at PTPN III Nusantara, totaling 100 MSMES business actors who were declared successful in MSMEs development. The sampling technique used was a saturated canoe. So that the sample in this study is 100 MSMES business actors. The data was collected using a questionnaire that was compiled based on each variable indicator item. The data analysis technique used Structural Equation Modeling with Smart PLS. The results showed that the direct use of social media and perceived competitive value and partnerships had a direct effect on the performance of MSMEs at PTPN III Nusantara. Indirectly, only partnerships do not have a role in mediating the use of social media on the performance of MSMEs. However, partnerships have a role in mediating perceived competitive value on the performance of MSMEs.